Surface Coordination and Polymerization of Allyl Mercaptan Passivates the Oxidation of Copper - Jiahao Yang; Xiaomeng She; Song Zhang; Ruixuan Qin; Dongming Cheng; Jian Peng (Advanced Materials Interfaces, 2025)
Abstract The oxidation of copper significantly restricts its widespread industrial applications. Traditional methods, such as alloying and anti‐corrosion coatings, often compromise copper's electrical and thermal conductivity. Molecular passivation technology has emerged as a promising solution, enhancing copper's anti‐corrosion properties without degrading its intrinsic physical characteristics. However, the enhancement of copper's anti‐corrosion properties through molecular passivation is far from satisfactory. Herein, allyl mercaptan is employed as a molecular passivation monomer to investigate its anti‐corrosion performance. It is demonstrated that allyl mercaptan can coordinate and polymerize on copper surfaces under mild conditions, forming polymeric passivation layers. The modified copper foil (Cu‐AM) exhibits a corrosion‐inhibiting efficiency of 99.65%. Density functional theory (DFT) calculations indicate that the coordination of allyl mercaptan on various copper crystal planes is spontaneous, with the dissociation adsorption energy ranking as Cu(100) > Cu(110) > Cu(111). Anti‐corrosion experiments on single‐crystal copper foils further corroborate these findings, showing that Cu(100)‐AM achieves the highest corrosion‐inhibiting efficiency of 99.91%.